Nonequilibrium transport through magnetic vibrating molecules - Roura Bas, Pablo Gines (2013)
We calculate the nonequilibrium conductance through a molecule or a quantum dot in which the occupation of the relevant electronic level is coupled with intensity λ to a phonon mode and also to two conducting leads. The system is described by the Anderson-Holstein Hamiltonian. We solve the problem using the Keldysh formalism and the noncrossing approximation for both the electron-electron and the electron-phonon interactions. We obtain a moderate decrease of the Kondo temperature TK with λ for fixed renormalized energy of the localized level Ed̃. The meaning and value of Ed̃ are discussed. The spectral density of localized electrons shows, in addition to the Kondo peak of width 2TK, satellites of this peak shifted by multiples of the phonon frequency ω0. The nonequilibrium conductance as a function of bias voltage Vb at small temperatures also displays peaks at multiples of ω0 in addition to the central dominant Kondo peak near Vb=0.